Role of Headmasters, Teachers, and Supervisors in Knowledge Transfer about Occupational Health and Safety to Pupils in Vocational Education - Ing-Marie Andersson; Kristina Gunnarsson; Gunnar Rosèn (Elsevier, 2015)
Background: Young people are at an increased risk for illness in working life. The authorities stipulate certain goals for training in occupational health and safety (OHS) in vocational schools. A previous study concluded that pupils in vocational education had limited knowledge in the prevention of health risks at work. The aim of the current study, therefore, was to study how OHS training is organized in school and in workplace-based learning (WPL). Methods: The study design featured a qualitative approach, which included interviews with 12 headmasters, 20 teachers, and 20 supervisors at companies in which the pupils had their WPL. The study was conducted at 10 upper secondary schools, located in Central Sweden, that were graduating pupils in four vocational programs. Results: The interviews with headmasters, teachers, and supervisors indicate a staggered picture of how pupils are prepared for safe work. The headmasters generally give teachers the responsibility for how goals should be reached. Teaching is very much based on risk factors that are present in the workshops and on teachers' own experiences and knowledge. The teaching during WPL also lacks the systematic training in OHS as well as in the traditional classroom environment. Conclusion: Teachers and supervisors did not plan the training in OHS in accordance with the provisions of systematic work environment management. Instead, the teachers based the training on their own experiences. Most of the supervisors did not receive information from the schools as to what should be included when introducing OHS issues in WPL.